Effect of Cracking on Corrosion of Steel in Concrete - Shaikh, Faiz (Springer, 2018)
© 2018, The Author(s). It is generally recognized that cracks provide easy access to ingress of chlorides in concrete and hence, the initiation of corrosion of steel in cracked concrete occurs at early stage. However, wide variety of results on the effect of crack widths on corrosion of steel in concrete are reported in many studies. Apart from crack width, the crack depths, cracking frequency and healing of cracks also influence the corrosion of steel in concrete. This paper presents a comprehensive review and summarised the results on the effect of cracking on corrosion of steel in concrete. The effect of crack widths on the diffusion of chlorides ions and carbon-dioxide is also discussed in this paper. Among all available results, a correlation between the corrosion current and the crack widths up to 0.3 mm can be established, however, no distinct trends are observed beyond that crack width. Conflicting results on the effect of crack widths on chloride ion diffusion are also reported. The longitudinal crack causes more severe corrosion of steel in concrete than transverse cracks of same width. Cracked concrete containing supplementary cementitious materials exhibited superior corrosion resistance than cracked ordinary Portland cement concrete of same width of transverse as well as longitudinal cracks. The same is also true in the case of lower water–binder ratios of cracked concrete. The increase in crack depth increased the chloride diffusion; however, the corrosion test shows an opposite trend. Conflicting results on the effect of crack frequency on corrosion of steel are also reported.